Kepemimpinan Transformatif Kiai Dalam Sistem Pendidikan Pesantren Salaf Di Pondok Pesantren Nurul Qadim Kabupaten Probolinggo - Rosidah, Kolifatur; Abdilah M, Fardan; Taufani, Taufani; Syahrul, Syahrul; Halil, Citra Buana (LPPM IAIN Sorong, 2025)
This study approach is qualitative. The study used a Phenomenology approach. The primary data source of this study was KH. Hafidzul Hakim Noer as the main informant and the ustad and administrators of the Islamic boarding school and the male and female students as additional informants. The secondary data sources of this study were the Islamic boarding school Work Program and the kaleidoscope documentation of the transformative journey of the Islamic boarding school. Data collection methods were observation, interviews and documentation. Data analysis included data reduction, presentation, and verification, and drawing conclusions.The findings indicate that the Kiai’s transformative leadership in the Salaf Education system at the Nurul Qadim Islamic Boarding School in Probolinggo Regency 1) involves all components of the management. Kiai never forces administrators beyond the capabilities. Kiai invites everyone to fight for common goals based on the capabilities of each boarding school personnels. Kiai provides examples and directions based on a concept of 3 components. Ta`rif, Ta`lif and Taklif. 2) In the implementation of transformative leadership, the kiai becomes a charismatic figure and acts transformatively in preparing plans and determining all decisions for the success and sustainability of Education at the Islamic boarding school. This is also supported by adequate human resource synergy in innovating to advance the Islamic boarding school